ENVIRONMENTAL PERFORMANCE, PROFITABILITY, AND LEVERAGE ON STOCK RETURN - Valensia, Regina; Yanti, Yanti (International Journal of Application on Economics and Business, 2024)
This research aims to evaluate the influence of environmental performance, profitability, and leverage on stock return in energy companies listed on the Indonesia Stock Exchange. Purposive sampling method was employed, utilizing data from 82 samples across 17 energy companies during the 2018 to 2022. Samples were gathered and processed using Microsoft Excel 2019 and IBM Statistics Version 20. This research indicates that profitability has a positive and significant impact on stock return, while environmental performance and leverage do not significantly affect stock return. The adjusted R2 value of 9.3% suggests that there are still other factors influencing stock return within the regression model. This research provides valuable insights for stakeholders in understanding the factors influencing stock return in energy companies.